Explicit Versus Implicit Instruction: A Meta-Analysis of Comparative Studies - 맹은경 (현대영어교육, 2020)
Previous meta-analyses provided inclusive results related to the effectiveness of explicit instruction (EI) and implicit instruction (II). However, the preceding meta-analyses did not afford a robust comparison of two types of instruction, as the data were not drawn from the same population. This meta-analysis study, therefore, aims to provide reliable comparative effectiveness on EI and II in Korean English classrooms. The study also aims to investigate moderating effects (outcome domains, modes, types, educational contexts, L2 proficiency, and duration of instruction) on comparative effectiveness of EI and II. 143 samples from 40 primary studies were coded into the CMA software to calculate eff ect sizes by computing Hedges’ g. This meta-analysis revealed a positive overall comparative effect of EI over II; EI is more effective than II in Korean English classrooms. Among six moderating variables only one variable showed a significant moderating effect on the comparative effectiveness of EL and II; EI is more effective for developing cognitive abilities and grammar and vocabulary knowledge than II. Findings and pedagogical and research implications are discussed.
Keywords: 명시적 학습; 암시적 학습; 측정유형; L2 능력; 메타분석; explicit instruction; implicit instruction; outcome type; L2 proficiency; meta-analysis